La « huitième saison » de la traduction. Quelques propos sur la traduction collective et les nouvelles pratiques traductionnelles de l’ère numérique - Rachwalska von Rejchwald, Jolanta (Studia Romanica Posnaniensia, 2019)
In the world 2.0, dominated by Big Data and transmedia, the figure of a translator who is alone with the complexities of the text seems to be replaced by group translations. Our era, which has become “cocreative”, “co-participative”, promotes collective behavior (such as coworking and crowdsourcing), also those in the field of translation. The practice of joint translations may take the form of funsubbing, which amateur translators are passionate about, but it is increasingly entering university walls (joint translations of the plays or participatory transcription of G. Flaubert’s manuscripts). It is possible that the meaning to be conveyed is no longer the main driver of the activities of this new generation of collaborating translators and that there are also other goals that collaborating translators put together. This article is an attempt to describe and understand this new translation practice and its role in disseminating knowledge and culture.